IMPLEMENTATION OF STUDENT-CENTERED LEARNING APPROACH AND TEACHER-CENTERED LEARNING APPROACH TOWARD MARITIME ENGLISH STUDENTS IN LANGUAGE LABORATORY PRACTICES: AN ACTION RESEARCH - Sri Sartini (Sekolah Tinggi Maritim Yogyakarta, 2016)
This research was conducted in an attempt to investigate teaching strategies concerning to both student-centered learning strategy and teacher-centered learning strategy. It is concerned toward teaching strategies implemented by the EFL lecturer, similarities and differences of teaching strategies applied, and problems encountered by the teachers in implementing the strategies. The settings of this research were Yogyakarta Maritime Academy with Nautical Science students Academic year 2015/2016 as the object of the study. The subjects of this research was the author who taught Maritime English Subject. This research was designed as a qualitative-quantitative research. The data were collected through questionnaire, observation, and document study. Data were analyzed by using Williamson (2008) and Celce-Murcia( 2001) EFL teaching strategies. Based on the data analysis, this study identified some findings. Student-centered learning approach which uses back-chaining drill was different in the implementation with that of teacher-centered learning approach using direct instruction. Back-chaining drill left enthusiatic experiences for students in learning process. The problems which occured were also different. In back-chaining mostly the problem was at the beginning of the activities and it led to enthusiastic and interesting material. However in direct instruction, it left monotonous activities.